Efficacy and safety of ertugliflozin across racial groups in patients with type 2 diabetes mellitus. (2nd August 2020) - Liu, Jie; Tarasenko, Lisa; Pong, Annpey; Huyck, Susan; Wu, Larry; Patel, Shrita; Hickman, Anne; Mancuso, James P.; Gantz, Ira; Terra, Steven G.
Abstract: Objective: To assess the efficacy and safety of the sodium–glucose cotransporter 2 inhibitor ertugliflozin across racial groups in patients with type 2 diabetes mellitus (T2DM). Methods: Pooled analysis of data from randomized, double-blind studies in the ertugliflozin phase III development program. Seven placebo- and comparator-controlled studies were used to assess safety ( N  = 4859) and three placebo-controlled studies were used to assess efficacy ( N  = 1544). Least-squares (LS) mean change from baseline was calculated for glycated hemoglobin (HbA1c), body weight and systolic blood pressure (SBP). Safety evaluation included overall and prespecified adverse events (AEs). Results: At Week 26, ertugliflozin provided a greater reduction in HbA1c, body weight and SBP versus placebo in all racial subgroups. The placebo-adjusted LS mean change (95% confidence interval) from baseline in HbA1c was −0.8% (−1.0, −0.7) and −1.0% (−1.1, −0.8) with ertugliflozin 5 mg and 15 mg, respectively, in the White subgroup, −0.7% (−1.2, −0.2) and −0.8% (−1.3, −0.3) in the Black subgroup, and −0.8% (−1.1, −0.5) and −1.0% (−1.3, −0.8) in the Asian subgroup. The incidences of overall AEs, serious AEs and AEs leading to discontinuation from study medication were similar between the ertugliflozin 5 mg, 15 mg and non-ertugliflozin groups within each racial subgroup. The incidence of female genital mycotic infection (GMI) was higher with ertugliflozin than non-ertugliflozin across all racial subgroups. The incidence of male GMI was higher with ertugliflozin than non-ertugliflozin in the White sub-group; however, there were few male GMI events in the non-White subgroups. Conclusions: In patients with T2DM, treatment with ertugliflozin improved HbA1c, body weight and SBP across all racial subgroups. Ertugliflozin had a generally similar safety profile across racial subgroups and was generally well tolerated. Clinicaltrials.gov identifiers: NCT01986855, NCT01999218, NCT01958671, NCT02099110, NCT02036515, NCT02033889, and NCT02226003.